Assessment of Cytotoxic, Genotoxic, and Oxidative Stress of Dibutyl Phthalate on Cultured Bovine Peripheral Lymphocytes. (24th March 2022) - Ali, Muhammad Muddassir; Sahar, Taha; Firyal, Sehrish; Ijaz, Muhammad; Majeed, Khalid Abdul; Awan, Furqan; Adil, Memoona; Akbar, Haroon; Rashid, Muhammad Imran; Ciğerci, İbrahim Hakki
Abstract : Recently, there have been numerous reports showing that phthalates have negative human health impacts and may cause several diseases such as asthma, breast cancer, obesity, type II diabetes, and male infertility. Animals are also exposed to phthalates through the environment and can cause adverse health effects on them. Several studies have been found on the cytogenetic effects of dibutyl phthalate (DBP) on different organisms but no documented evidence has been found on the cytotoxic and genotoxic effects of dibutyl phthalate (DBP) on bovine cultured lymphocytes. MTT assay was performed on different series of DBP concentrations (10  μ M, 20  μ M, 30  μ M, 50  μ M, 70  μ M, 100  μ M). A concentration-dependent decrease in cell viability was observed by the DBP. The LD50, LD50/2, and 2∗ LD50 were found to be 50  μ M, 30  μ M, and 80  μ M on bovine lymphocytes, respectively. Then, these concentrations of DBP were utilized to perform comet, micronucleus assays, and oxidative stress. A concentration-dependent increase in DNA damage, oxidative stress, and micronuclei formation was observed in lymphocytes by the DBP as compared to the control group. Highest genotoxic effects were observed at a concentration of 2∗ LD50. Similarly, total oxidative stress was found higher, and antioxidative stress was lower in concentration-dependent manner by the DBP. The current study revealed a significant cytotoxic, genotoxic, and oxidative stress of DBP on cultured bovine lymphocytes.